Solid-state foaming of acrylonitrile butadiene styrene through microcellular 3D printing process. (March 2022) - Dugad, Rupesh; Radhakrishna, G; Gandhi, Abhishek
The lightweight products with superior specific strength are in great demand in numerous applications such as automotive, aerospace, biomedical, sports, etc. This work focussed on the manufacturing of lightweight products using the cellular three dimensional (3D) printing process. In this work, the continuous microcellular morphology has been developed in a single foamed filament using 3 D printing of carbon-di-oxide (CO2 ) saturated acrylonitrile butadiene styrene (ABS) filaments. The microcellular structures with average cell size in the range of 6–1040 µm were developed. The influence of printing parameters; nozzle temperature, feed rate, and flow rate on the foam characteristics and cell morphology at different levels were investigated. The different kinds of observed foamed extrudate irregularities were discussed.